SWING-UP CONTROL OF MASS BODY INTERLINKED FLEXIBLE TETHER - ABDULLAH, Mohd Azman; MICHITSUJI, Yohei; Takehara, Shoichiro; NAGAI, Masao; Miyajima, Naoki (2010)
One of the applications of tether system is in the field of satellite technology, where the mother ship and satellite equipment are connected with a cable. In order to grasp the motion of this kind of tether system in detail, the tether can be effectively modeled as flexible body and dealt by multibody dynamic analysis. In the analysis and modeling of flexible body of tether, large deformation and large displacement must be considered. Multibody dynamic analysis such as Absolute Nodal Coordinate Formulation with an introduction of the effect of damping force formulation can be used to describe the motion behavior of a flexible body. In this study, a parameter identification technique via an experimental approach is proposed in order to verify the modeling method. An example of swing-up control using the genetic algorithm control approach is performed through simulation and experiment. The validity of the model and availability of motion control based on multibody dynamics analysis are shown by comparison between numerical simulation and experiment.